Mitigation of Voltage Disturbances in Industrial Power Distribution Networks Using Dynamic Voltage Restorers - Mnkeni, Godwin E.; Justo, Jackson J.; Mushi, Aviti T.; Mwinyiwiwa, Bakari M. M. (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Most electrical and electronic equipment in industries require highquality power to function efficiently. Nonetheless, voltage sags and <span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">swells are pressing concerns and prone to directly impact the economy of industrial customers. One such customer embattled with these problems is Mbeya Cement Company Limited (MCC) located in Mbeya, Tanzania. These issues mainly are caused by upstream faults and switching operations. One way to address these is by utilizing the voltage injection method, which employs a power device known as a dynamic voltage restorer (DVR). In this paper, the voltage sags and swells of balanced three-phase, unbalanced double-line and single-line to ground faults are studied. Thereafter, mitigation strategies using the DVR are proposed for the MCC. A section of the MCC power distribution network fed from Tanzania Electric Supply Company Limited (TANESCO) Mwakibete substation with a 33 kV feeder is modeled using MATLAB/Simulink environment to mitigate the disturbances (sags/swells). The percentage of voltage sags and swells logged from the industrial feeder are 11 and 115%, respectively. To effectively utilize the DVR device, a control strategy is designed in the d-q-o reference frame, whereby the scaled errors between the source side of the DVR and its references for sags/swells corrections are considered. Simulation results revealed that the DVR performance handles both balanced and unbalanced voltage sags and swells by injecting the appropriate voltage to the supply, therefore, maintaining the load voltage at its nominal value. It can be concluded that the DVRs are recommended to be incorporated into the MCC feeders to mitigate the upstream disturbances. However, DVR performance comes at the cost of energy storage and DVR transformer rating. Further studies are encouraged to focus on the DVR performance optimization and cost implications.